Sistemas administrativos y su relación con la productividad de la Gerencia Sub Regional De Ucayali Contamana 2025 - Romero Labajos, Lessep (2025)
The study sought to determine the relationship between administrative systems and productivity in the Sub-Regional Management of Ucayali Contamana 2025. To achieve this goal, a fundamental methodology was used, with a descriptive-correlational approach and a non-experimental design. The research sample included 98 administrative employees. The findings revealed that 40% of respondents classified the administrative system as average. This result is attributed to the fact that the resources and assets necessary for the fulfillment of functions were available in a timely manner. Furthermore, effective coordination between the areas involved in institutional procurement was occasionally perceived. Regarding labor productivity, 38% of respondents considered it to be average, stating that they almost always made optimal and appropriate use of the resources allocated by the institution. However, they acknowledged that they only occasionally shared important and necessary information with their colleagues during the execution of their work activities. Ultimately, a strong connection between administrative systems and labor productivity was revealed, supported by a Spearman coefficient of 0.957 and a two-tailed significance of 0.01. Furthermore, it was observed that the different administrative systems exhibited significant correlations with labor productivity: the National Supply System obtained a coefficient of 0.778; the National Accounting System, 0.846; the National Treasury System, 0.889; and the National Budget System, 0.776. In all cases, the two-tailed significance was 0.000, confirming their statistical significance.